Financial Inclusion Through Digitalization (Trinity Journal of Management, IT & Media (TJMITM), 2016)
This paper study about basic concept of financial inclusion and  its role in providing services to the weaker section of society at  reasonable prices with digital mode. Here the study comprises  how the digital era seems to one of lower cost prospect which  helps in balancing economic and financial aspects, improving  employment opportunities further adds national income and  economic development of a nation. This paper shows highlights of  the vision initiated by Government of India as a provision focuses  upon digital empowerment & good governance and the initiatives  taken under digital technology in order to spread awareness and  its usage among the masses . This paper is descriptive in nature.
Keywords: Financial Inclusion; Digital empowerment